Analysis of Constitutional Court Decisions Regarding the Executorial Power of Fiduciary Guarantee Certificates - Anggreani Arief (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The executive power over Fiduciary Guarantee Certificates in its implementation creates many problems. According to the provisions of Article 15 section (2) and section (3) of the Fiduciary Guarantee Law, which in essence states that the Fiduciary Guarantee Certificate has the same executive power as a court decision that has obtained permanent law, if the debtor defaults, the creditor as the fiduciary recipient has the right to sell the collateral object fiduciary. The fiduciary recipients have often used the statement as an excuse to sell collateral objects unilaterally without going through proper legal procedures to the detriment of the fiduciary giver. This research aims to analyze the legal reasons of the applicant and the ratio decidendi of the Constitutional Court's Decision. The research method is normative legal research through the use of primary data and secondary data, which is analyzed in a qualitative method and shown descriptively. Based on the results of the research, as regulated in Article 15 section (2) and section (3) of the Fiduciary Guarantee Law, the content should further restrict the execution procedure so that it can be carried out under the execution mechanism of a court decision with permanent legal force. Ratio decidendi Constitutional Court Decision No. 18/PUU-XVII/2019 is given conditions for fiduciary guarantees, that implementation of the Fiduciary Guarantee Certificate must be conducted and apply the same as executing court decisions that have permanent legal force